Fragilidade de idosos em contexto de vulnerabilidade social - Jesus, Isabela Thaís Machado de (2017)
Introduction: Aging accompanied by frailty can burden services in basic protection and primary care that assist the elderly population. Assessing the frailty in the elderly in a context of social vulnerability can contribute to the improvement of the quality of social facilities that care for the elderly. Objective: To analyze the frailty of elderly people living in neighborhoods with social vulnerability and enrolled in Social Care Referral Centers (CRAS) in relation to quality of life, cognition, family and external relations in a city in the interior of the State of São Paulo. Methods: Exploratory, comparative and transversal study, using the quantitative research method. This study used and expanded the database of the research entitled "The frailty of the elderly and the Basic Attention System of Social Assistance". In the study were: semi-structured evaluation; Edmonton Frailty Scale to check for frailty; Whoqol-bref and Whoqol-old to check the quality of life; The Montreal Cognitive Assessment for screening for cognitive impairment; Genogram to check the family relations and Ecomapa to check the external relations. Data were analyzed using descriptive statistics, Spearman correlation test and comparison test of Mann-Whitney and Kruskal- Wallis groups. Results: Participated of the study 247 elderly people, with a mean age of 68.52 (dp = 7,28) years, 154 were white (57,49%), 109 married (44,13%), 109 catholic (61,13%), 137 retired (55,47%) and 133 with education of one to four years (53,85%). Regarding the level of frailty, 41,70% did not present frailty, 21,45% were vulnerable and 36,84% presented frailty at some level. Of the 247 participants, 58,29% lived in regions with high vulnerability. There was a negative correlation between the frailty and vulnerability (r:-0,4936;p:0,4936), quality of life (Whoqol-bref r:-0,50307;p<0,0001; Wholqol-old r:-0,43951;p<0,001) and cognition (r:-0,21690;p:0,0006). There was a statistically significant difference between the frailty and external relationship quantity (p<0,001). Conclusion: It was found that the frailty elderly lived in more vulnerable regions. Knowing the frailty of the elderly in a context of social vulnerability may help in the management and implementation of actions of public welfare services directed to this population segment. Frailty screening should be integrated into both services and research because the evaluation consists of alert for initial risk identification.